Prevalence and prognosis of patients with lone and paroxysmal atrial tachyarrhythmias showing Brugada‐type electrocardiograms after class IC antiarrhythmic drug administration but no risk‐stratifying factors. Issue 2 (21st March 2013) - Abe, Atsuko; Fujino, Tadashi; Fukunaga, Shunji; Yuzawa, Hitomi; Sato, Hideyuki; Suzuki, Takeya; Kobayashi, Kenzaburo; Okano, Yoshifumi; Nakamura, Kentaro; Yusu, Satoru; Yoshino, Hideaki; Ashihara, Takashi; et al.
Abstract: Background: Class IC antiarrhythmic drugs, used to prevent paroxysmal atrial tachyarrhythmias (ATs), are well known to effectively unmask the electrocardiogram (ECG) pattern of Brugada syndrome. We used these drugs to investigate the prevalence and prognosis of patients with lone and paroxysmal ATs and Brugada‐type ECGs. Methods and results: We enrolled 702 consecutive patients who were given class IC antiarrhythmic drugs (pilsicainide or propafenone) to inhibit paroxysmal ATs. We analyzed 12‐lead ECGs before and after drug administration using a computerized ECG system. A Brugada‐type ECG was defined as a coved pattern of ST segment elevation (>0.2 mV) in leads V 1 − V 2 . No patients had risk‐stratifying factors of the syndrome. Forty‐four patients (6.3%) had significant ST‐segment elevation in leads V 1 − V 2 after drug administration. Among these patients, a coved ECG pattern was observed in 10 (1.4%). The use of pilsicainide ( n =9) was significantly ( P =0.02) greater than that of propafenone ( n =1). During the follow‐up period of 85±19 months, none of the 10 patients had ventricular tachyarrhythmias. Conclusions: Manifestation of Brugada‐type ECGs by class IC antiarrhythmic drugs is neither rare nor serious in patients with lone and paroxysmal ATs but without risk‐stratifying factors for the syndrome.